Locating causes of abnormality of EPG experience based on decision tree - Xiaomin TAN; Ai FANG; Bing LIANG; Haojie YANG (Dianxin kexue)
Improving user experience has always been the focus of IPTV operation.However,IPTV network is relatively complex,including multiple scheduling links such as set-top box,access network,EPG page,EPG server and media server.Once the abnormality occurs,monitoring indicators of each link will be checked to locate the cause of abnormality by human experience.The operation mode relies on professionals,which is inefficient and unable to stop losses quickly.Thus,to solve the problem above,based on big data technology,decision tree was implied to locate the cause of abnormality according to the classification rule of the tree model.Decision tree model has been used in actual networks of IPTV and helps to find out the cause of abnormality,which improves the efficiency of operation.